Kontribusi Psikoterapi Islam bagi Kesehatan Mental - Andini, Mutiara; Aprilia, Djumi; Distina, Primalita Putri (Psychosophia: Journal of Psychology, Religion, and Humanity, 2021)
The concept of health based on religion has a long-term concept that is not only oriented, but can be used over time. Religion can have a significant impact on human life, including on health. One of the solutions to be able to overcome mental health problems is to practice religious values ​​in everyday life. The purpose of this study is to explain further about Islamic Psychotherapy in improving mental health by looking at the nature of mental health based on or referring to the Qur'an and Al-Hadith. The methods of this research were using literature review on various journal sources and analytical readings that collected through Islamic Psychotherapy, Mental Health, Al-Qur'an and Al-Hadith keyword. The results of this study indicated that Islamic psychotherapy is the most effective effort to cure and prevent mental illness. Islamic psychotherapy believed that faith and closeness to the Creator will be a very significant force for the good of one's mental problems. Islamic psychotherapy was not only treating people with physical and spiritual illnesses, but also improving one's mental quality to achieve a happy life. Thus, in result the mental health would be achieving harmony, tranquility, well-being, and peace of mind.